Analysis of frictional stresses and wear in the contact pair of a vehicle current collector - Kovtun, O.S.; Holenko, K.E.; Ganzyuk, A.L.; Dykha, M.O.; Dytyniuk, V.O. (Problems of Tribology, 2025)
The article presents the results of numerical modeling of the operation of the trolleybus current collector pair "contact insert - wire" using the Ansys software environment. The distribution of frictional stresses (Frictional Stress) and contact pressures for two types of insert materials is analyzed: electrographite (Electrographite, parallel to plane) and copper-graphite composite Cu–40%C(f) 0.90 laminate. It was established that the real area of the contact spot is smaller than the entire surface of the gutter, which significantly affects the calculated values of the average frictional stresses and, accordingly, the wear forecast. For the electrographite insert, the average value of Frictional Stress was 0.439 MPa, for the copper-graphite insert – 0.599 MPa. The calculations showed that at a mileage of 450 km, the wear of the electrographite insert exceeds the permissible value, while for the copper-graphite one it is 2.1564 mm and is within the normal range. However, due to the higher hardness of the copper-graphite material compared to the copper wire, the wire itself can become the main element of wear, which is undesirable. It was concluded that the optimal option may be to use a material with intermediate hardness, which will provide a balance between the wear resistance of the insert and the preservation of the contact wire resource.